The influence of green marketing campaigns and brand ambassadors on the body shop's product purchase decisions - Rediyono, Rediyono (SEAN Institute, 2024)
The aim of this research is to determine the influence of green marketing campaigns and brand ambassadors on product purchasing decisions for The Body Shop users. This type of research is quantitative and carried out using a survey method. Data was obtained by distributing questionnaires to 100 respondents. The respondents in this research were students in the Jabodetabek area. This research uses multiple linear regression analysis methods using SPSS version 23. The research results show that the Green Marketing Campaign has a positive and significant influence on consumer purchasing decisions. Meanwhile, the use of Brand Ambassadors does not have a significant influence and is not the main factor in influencing purchasing decisions made by consumers.